2021
DOI: 10.3390/ijms22031135
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory Effects of Indoxyl Sulfate in Mice: Impairment of Intestinal Homeostasis and Immune Response

Abstract: The intestines are recognized as the main source of chronic inflammation in chronic kidney disease (CKD) and, among other cells, macrophages are involved in modulating this process as well as in the impaired immune response which also occurs in CKD patients. In this study, we evaluated the effect of Indoxyl Sulfate (IS), a protein bound uremic toxin poorly eliminated by hemodialysis, on inflammatory, oxidative stress and pro-apoptotic parameters, at the intestinal level in mice, on intestinal epithelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 70 publications
2
35
0
Order By: Relevance
“…No: M1U539 G, L10, Bio-Optica, Milan, Italy). The following primary antibodies were used: Polyclonal Rabbit Anti-CD3 (Code n. ab5690, Abcam, Cambridge, UK) at 1:100 in PBS, Monoclonal Mouse Anti-CD79 (Clone HM57, Dako, Santa Clara, CA, USA) at 1:100 in PBS, and Polyclonal Rabbit Anti-Iba1 (Code n. 019-19741, WAKO, Osaka, Japan) at 1:1000 in PBS [ 34 ]. Slides were examined and photographed with a light microscope (Nikon Eclipse E600 Tokyo, Japan) equipped with a microphotography system Nikon digital camera (DMX1200 Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…No: M1U539 G, L10, Bio-Optica, Milan, Italy). The following primary antibodies were used: Polyclonal Rabbit Anti-CD3 (Code n. ab5690, Abcam, Cambridge, UK) at 1:100 in PBS, Monoclonal Mouse Anti-CD79 (Clone HM57, Dako, Santa Clara, CA, USA) at 1:100 in PBS, and Polyclonal Rabbit Anti-Iba1 (Code n. 019-19741, WAKO, Osaka, Japan) at 1:1000 in PBS [ 34 ]. Slides were examined and photographed with a light microscope (Nikon Eclipse E600 Tokyo, Japan) equipped with a microphotography system Nikon digital camera (DMX1200 Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…IS exposure has been reported to increase pro-oxidation and pro-inflammatory reactions in a mouse study [ 30 ]. In our study, the results showed that both ROS scavenging and blockade of the MAPK pathway significantly reduced the mRNA levels of the proinflammatory genes il-1b and cox2a, whose expression was induced by IS ( Figure 6 ), suggesting that IS may cause inflammation through oxidative stress and the MAPK pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a mouse-based model study investigating IS-induced oxidative stress revealed that a significant fluorescence signal of H2DCF-DA (an H 2 O 2 -sensitive fluorescent probe) was detectable in primary mouse peritoneal macrophages after 3 h and 6 h of IS treatment, and the expression of the antioxidant enzyme SOD-2 was reduced [ 30 ]. Additionally, another study showed that injection of unilaterally nephrectomized mice with IS significantly increased the levels of the lipid peroxidation indicator malondialdehyde (MDA) in mouse urine and serum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IS stimulates oxidative stress [ 125 , 126 , 127 , 128 ], whereby contributing to endothelial senescence [ 129 ]. Several studies focused on proinflammatory properties of IS [ 130 , 131 ] and its influence on the function of macrophages [ 132 , 133 , 134 ], with the latter aspect linking IS to the development of atherosclerosis. Clinical studies in adult people constituted IS as an important compound related to the progression of CKD, associated CVD, infections, glucose intolerance and mortality [ 117 , 135 , 136 , 137 , 138 , 139 , 140 ].…”
Section: Pathogenesis Of Ckd-aimentioning
confidence: 99%